Consensus Analysis of Second-Order Multiagent Systems with General Topology and Time Delay - Bo Liu; Guangming Xie; Yanping Gao; Jiaxi Wu; Jianguo Zhang; Wenguang Luo (Journal of Applied Mathematics)
This paper addresses the consensus of second-order multiagent systems with general topology and time delay based on the nearest neighbor rule. By using the Laplace transform technique, it is proved that the second-order multi-agent system in the presence of time-delay can reach consensus if the network topology contains a globally reachable node and time delay is bounded. The bound of time-delay only depends on eigenvalues of the Laplacian matrix of the system. The main contribution of this paper is that the accurate state of the consensus center and the upper bound of the communication delay to make the agents reach consensus are given. Some numerical simulations are given to illustrate the theoretical results.